P‐211L: Late‐News Poster: Exploring the Pixel Density Limitations of SBS AMOLED for VR Application. Issue 1 (May 2016) - Chen, Yu-Hung; Hsin, Meng-Hung; Chen, Yi-Chi; Su, Yi-Hao; Chen, Wen-Tai; Chen, Teng-Ke; Chen, Tsu-Wei; Yang, Shun-Ping; Lee, Chien-Ya; Lin, Hong Shen; Chen, Peng-Yu; Chen, Kuo-Kuang; et al.
Abstract : Fine metal masks (FMM) have always been a critical manufacturing tool for the fabrication (SBS) AMOLED panels. In this work, we suocfc eRs/sGfu/lBly fsaibdrei‐cbayt‐esidd ae ssterruiecst uoref tOo LcEonDf irdmev itchees maanndu faacctitvuer inmga fteriaxs ipbailniteyl sw iitnh oau th uysbirnigd pFeMrfoMrm taonolcse. s Fharovme coomupr ateixbplee rliifme‐etnimtael trdeantad, s aanlld othfe tshaem ed eJvVicBe characteristics after photolithography process.